MEKANISME PENGAWASAN TERHADAP PERATURAN DAERAH MENURUT UNDANG-UNDANG NOMOR 32 TAHUN 2004 - Herma Yanti (Jurnal LEX SPECIALIS, 2010)
During the the year of 1998 issue of decentralization has becoming polemic in Indonesia, the province ask more autonomy from central goverment, but more autonomy doent meant give the final solution it require more system about check and watch to every aspect of goverment act, so the goverment can work with properly with good mechanism as a public servant just like Act No 32 Year 2004 want to reach. Keyword : Check and watch mechanism of Act No 32 Year 2004